Indirect cytotoxicity of a 35% hydrogen peroxide bleaching gel on cultured odontoblast-like cells - Coldebella, Cármen Regina [UNESP]; Ribeiro, Ana Paula Dias [UNESP]; Sacono, Nancy Tomoko [UNESP]; Trindade, Flávia Zardo [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (FapUNIFESP (SciELO), 2009)
The aim of this study was to evaluate the trans-enamel and trans-dentinal effects of a 35% hydrogen peroxide (H2O2) bleaching gel on odontoblast-like cells. Enamel/dentin discs obtained from bovine incisors were mounted in artificial pulp chambers (APCs). Three groups were formed: G1- 35% H2O2; G2- 35% H2O2 + halogen light application; G3- control. The treatments were repeated 5 times and the APCs were incubated for 12 h. Then, the extract was collected and applied for 24 h on the cells. Cell metabolism, total protein dosage and cell morphology were evaluated. Cell metabolism decreased by 62.09% and 61.83% in G1 and G2, respectively. The depression of cell metabolism was statistically significant when G1 and G2 were compared to G3. Total protein dosage decreased by 93.13% and 91.80% in G1 and G2, respectively. The cells in G1 and G2 exhibited significant morphological alterations after contact with the extracts. Regardless of halogen light application, the extracts caused significantly more intense cytopathic effects compared to the control group. After 5 consecutive applications of a 35% H2O2 bleaching agent, either catalyzed or not by halogen light, products of gel degradation were capable to diffuse through enamel and dentin causing toxic effects to the cells.
Keywords: Cytotoxicity; Hydrogen peroxide; Odontoblasts; Tooth bleaching; hydrogen peroxide; oxidizing agent; animal; cattle; cell culture; cytology; dental care; dentin; drug effect; enamel; odontoblast; tooth permeability; tooth pulp; topical drug administration; Administration, Topical; Animals; Cattle; Cells, Cultured; Dental Enamel; Dental Enamel Permeability; Dental Pulp; Dental Pulp Cavity; Dentin; Dentin Permeability; Hydrogen Peroxide; Oxidants; Tooth Bleaching